Women’s intention to enter top management in malaysia: a closer look at the “glass ceiling” phenomenon - Nurul Azwa Mohamed Khadri; Geetha Subramaniam (Faculty of Entrepreneurship and Business,UMK, 2015)
Malaysia has undergone a transformation over the past few decades as they move from a primarily agrarian society to modern industrial society. These economic changes have important implications on demographic and labour issues. Even though an increase in demand for a highly skilled workforce has seen more women enter the labor force, but the number of women at top management level is considerably very low. “Glass ceiling” in this study represents the barriers that women face to enter top management positions in the organization. Glass ceiling is categorized into two main categories in this study: (1) personal challenges that consist of demographic factors, family commitment and family support; and (2) work challenges that consist of negative stereotype, workplace arrangement, organizational culture and career development opportunities. The implications of this issue range from micro level, such as women’s dissatisfaction over the job opportunities and exiting from the labor force to macro issues such as brain drain and migration. This study aims to identify the main challenges that women face to enter top management positions in Malaysia either it is from personal challenges or work challenges. 300 respondents were selected in order to collect the data. Using cross-tabulation analysis and descriptive analysis, it was found that demographic factors, family commitment, organizational culture and career advancement opportunities have a more significant influence on women’s intention to enter top management. While family support, negative stereotype and workplace arrangements have less significant influence on women’s intentions to move up the career ladder. From the findings of this study, it can be concluded that the “glass ceiling” phenomenon that hinder women’s intention to enter top management in Malaysia come from both personal and employers’ challenges.